PENGAWASAN PARTISIPATIF DAN UPAYA MENINGKATKAN LEVEL DEMOKRASI KITA - Satria, Iqbal Reza; Rahman , M. Ridha Taufiq (Bawaslu Provinsi Jawa Barat, 2023)
The Election Supervisory Board (Bawaslu), mandated by the law as the leading actor in overseeing the electoral process, holds the potential to enhance the quality of elections, which correlates with the quality of democracy through a Participatory Oversight Program. Active participation of the community, a crucial aspect in elections, needs improvement to ensure that the quality of general elections elevates, both in procedural and substantive aspects. The trust of the public in the electoral process and its outcomes is a growing concern, as community participation has so far been limited to statistical figures. Utilizing qualitative research methods and analytical descriptive techniques In this article, we make a case for the potential of participatory oversight initiated by Bawaslu to enhance the community's role in ensuring fair and transparent elections. By using participatory approaches, public education, and technology, Bawaslu can engage the public and increase their awareness in ensuring integrity-driven elections, which can help boost the quality of our democracy